Practitioners' perceptions of the picture exchange communication system for children with autism. Issue 2 (16th January 2021) - Alsayedhassan, Batool; Lee, Jaehoon; Banda, Devender R.; Kim, Youngmin; Griffin-Shirley, Nora
Abstract: Backgound: Autism spectrum disorder impacts social-communication. Picture Exchange Communication System is one of the methods to improve communication skills in individuals with autism. In spite of numerous studies on the effectiveness of Picture Exchange Communication System, no studies were conducted to examine the perceptions of practitioners who used the strategy. Method: An online survey was conducted with 120 practitioners (44 teachers and 76 therapists; 80.8% 20–49 years old; 80.8% graduate education) who used the Picture Exchange Communication System with children with autism. Using rating scales, practitioners reported their knowledge of Picture Exchange Communication System and their perceptions about importance, benefits, and barriers of utilizing Picture Exchange Communication System. Results: Practitioners reported they were confident when implementing Picture Exchange Communication System and considered integrating Picture Exchange Communication System at school to be important. Also, the practitioners indicated that Picture Exchange Communication System was easy to use and effective to develop communication skills in children with autism. However, they found that using Picture Exchange Communication System was time consuming. Conclusion: It is important to hear the viewpoints of practitioners concerning the use of Picture Exchange Communication System for individuals with autism spectrum disorder. This study found Picture Exchange Communication System is a useful strategy but has some barriers concerning its use. Future research is needed to confirm the current findings with a larger sample. IMPLICATIONS FOR REHABILITATION: Many students with autism spectrum disorder are non-verbal and may benefit from augmentative and alternative communication methods. Picture Exchange Communication System, one of the augmentative and alternative communication methods, has been widely used by professionals and parents to improve communication skills of children with autism spectrum disorder who are non-verbal or have complex communication needs. Practitioners indicated that Picture Exchange Communication System was easy to use and effective to develop communication skills in children with autism spectrum disorder. However, they found that it is time consuming. Practitioners need ongoing support when implementing the Picture Exchange Communication System.